The Effect of Macroeconomic Variables on the Amount of Zakat Receipts in Indonesia - Siti Zubaidah; Ahmad Munawar (Universitas Pendidikan Indonesia, 2021)
AbstractPurpose – This study aims to explain the effect of macroeconomic variables on the number of zakat receipts in 2016-2020 at BAZNAS. Macroeconomic variables in this study consist of GDP per capita, inflation, and exchange rates.Methodology - The method used in this research is the quantitative method with multiple regression analysis models. The data used are secondary data from BI, BPS, and zakat financial reports in BAZNAS. Findings - This study indicates that the macroeconomic variables consisting of GDP per capita, inflation, and exchange rates do not affect the number of zakat receipts. The independent variables of GDP per capita, inflation, and the exchange rate can only explain their effect on the total zakat receipts of 36.91%. Other variables explain the remaining 63.09% outside of research.Keywords: GDP Per Capita; Inflation; Exchange Rate; Zakat.